Diagenetic fate of bioapatite in linguliform brachiopods: multiple apatite phases in shells of Cambrian lingulate brachiopod Ungula ingrica (Eichwald). (6th March 2015) - Lang, Liisa; Kirsimäe, Kalle; Vahur, Signe
Abstract : Fossil skeletal apatites vary in their composition and can yield mixed biochemical, environmental and diagenetic information. Thus, it is important to evaluate the diagenesis spatially inside the skeleton. We study the cross sections of shells of the Furongian lingulate brachiopod Ungula ingrica from Estonia using the Attenuated Total Reflectance – Fourier Transform Infrared (ATR‐FTIR) microspectroscopic and energy dispersive spectroscopic (EDS) mapping and show for the first time that different structural laminae of the shell have different chemical compositions. Compact laminae are rich in PO4 3−, Na, Mg and poor in F and Ca. Porous (baculate) laminae are rich in carbonate anions, Ca and F, but contain less Na and Mg. The ATR‐FTIR spectra show further differences in the ν 2 carbonate region, where the IR band at 872 cm −1 in compact laminae is replaced by a strong band at 864 cm −1 in baculate laminae. The changes in shell apatite suggest different origins of the apatite phases. Compact laminae are likely chemically less altered and could potentially carry more reliable palaeoenvironmental or geochemical information than the apatite in baculate laminae, which is mostly authigenic in its origin.